Cost Leadership Strategy: A New Game Strategy for Competitive Advantage in Milk Processing Firms in Kenya - Paul G. Kimiti; Stephen M. A. Muathe; Elishiba M. Murigi (European Scientific Journal, ESJ, 2021)
Competitive advantage refers to the benefits that firms accrue from unique combination of possessions to outperform competitors. To build competitive advantage as a gateway to superior performance, firms pursue various beneficial strategic orientations. This study sought to establish whether cost leadership strategy gave rise to competitive advantage in milk processing firms in Kenya. The authors utilized the indicators of economies of scale, economies of scope and operational efficiency to operationalize cost leadership strategy while competitive advantage was operationalized through capabilities and knowledge. A census of all the milk processing firms was conducted with 148 respondents participating in the study. Data was collected using semi-structured self-administered questionnaires and subsequently analyzed using descriptive and inferential statistics. The study concluded that cost leadership strategy was a source of competitive advantage for the milk processors. It therefore recommends pursuit of cost leadership strategy as a competitive tool. It further recommends building of relevant capabilities and protection of tacit knowledge by firms as foundational blocks for competitive advantage.